Critical Assessment of G Protein-Biased Agonism at the μ-Opioid Receptor. (December 2020) - Gillis, Alexander; Kliewer, Andrea; Kelly, Eamonn; Henderson, Graeme; Christie, Macdonald J.; Schulz, Stefan; Canals, Meritxell
Abstract : G protein-biased agonists of the μ-opioid receptor (MOPr) have been proposed as an improved class of opioid analgesics. Recent studies have been unable to reproduce the original experiments in the β-arrestin2-knockout mouse that led to this proposal, and alternative genetic models do not support the G protein-biased MOPr agonist hypothesis. Furthermore, assessment of putatively biased ligands has been confounded by several factors, including assay amplification. As such, the extent to which current lead compounds represent mechanistically novel, extremely G protein-biased agonists is in question, as is the underlying assumption that β-arrestin2 mediates deleterious opioid effects. Addressing these current challenges represents a pressing issue to successfully advance drug development at this receptor and improve upon current opioid analgesics. Highlights: G protein-biased agonists of the µ-opioid receptor have been hypothesized to be an improved class of opioid analgesics Early studies in the β-arrestin2-knockout mouse that suggested a separation between the signaling mediating analgesia versus side effects have not been reproduced, and a 'G protein-biased' mutant MOPr mouse does not support the original proposal. There is now evidence for a G protein-dependent signal mediating deleterious opioid effects. The previously observed G protein bias of many recently developed MOPr agonists has been confounded by assay amplification. Such ligands may in fact be unbiased, with low intrinsic efficacy. Current evidence does not support the proposal that G protein-biased agonism at the MOPr will provide substantially improved therapeutic profiles. Low intrinsic efficacy represents an alternative mechanism by which novel opioids may display wider therapeutic windows.